Prinsip Kemanusiaan Dan Pembatasan Kekerasan: Pendekatan Hak Asasi Manusia Global dan Islamic Sociological Jurisprudence Theory - Ahmad Muhamad Mustain Nasoha; Arsya Fahrezi; Lanang Elwas Khawaridzmi (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2026)
This study is motivated by the growing gap between the normative principle of humanity in global human rights law and the practice of limiting violence in increasingly complex contemporary conflicts, particularly in the context of asymmetric warfare and the use of modern technology. The objective of this research is to critically analyze the integration between the principle of humanity in international law—especially through the principles of proportionality and distinction—and the framework of Islamic Sociological Jurisprudence Theory, which is oriented toward maqāṣid al-syarī‘ah and substantive justice. This research employs a normative juridical approach using a literature study method with a conceptual and comparative analysis of various sources of international law and contemporary Islamic law. The findings indicate that the procedural and calculative nature of global human rights law has not fully addressed the complexity of humanitarian impacts in modern conflicts, thereby necessitating a more holistic approach. The integration with Islamic Sociological Jurisprudence Theory proves to enrich the analysis by emphasizing the protection of life, public welfare, and a substantive evaluation of the impacts of violence, both direct and long-term. The implications of this study highlight the importance of reconstructing a paradigm of violence limitation that is more adaptive, humanistic, and contextual through a synthesis of universal values and Islamic ethical-theological principles in order to strengthen the protection of human dignity in the contemporary era.